Two Heads Are Better Than One : Agricultural Production and Investment in Côte d’Ivoire - Donald, Aletheia; Goldstein, Markus; Rouanet, Léa (World Bank, Washington, DC, 2022)
Low levels of agricultural productivity and investment hinder economic growth in developing countries. This paper presents results from a field experiment in Côte d'Ivoire, which randomized wives’ participation in an agricultural extension training for rubber, a male-dominated export crop that takes six years to start producing latex but requires upfront care. The training included a planning portion, consisting of filling out an action plan for rubber farming over the next two years, and a skills portion. In the without-wife group, households witnessed a 26.4 percent drop in the value of the crop harvested and a 18.4 percent drop in productivity, with labor going to planting rubber seedlings. In the group with wife participation, households had higher levels of investment (planting 20 percent more rubber seedlings) and were able to maintain pre-program levels of agricultural production on older trees and other crops. These households increased their labor hours and agricultural input use, resulting in no drop in overall production or productivity. This outcome did not come through increased skills or incentives. Rather, underlying these results are increases in planned agricultural management by wives, increased retention of the action plan, and a reduction in gendered task division. The results show how including women in economic planning can improve the efficiency of household farm production and promote higher levels of investment.